NAGPRA in Archaeological Practice: Implementing Duty of Care - Jennifer R. Haas; Brooke Morgan; Ellen Lofaro; Jayne-Leigh Thomas; Sarah O’Donnell; Nina M. Schreiner; Miranda Panther (Advances in Archaeological Practice)
This article examines how Native Nations and institutions have been affected by a new directive in the revised NAGPRA regulations, the duty of care provision (43 CFR 10.1(d)), with a focus on the care of Indigenous Ancestral remains and cultural items. The Native Nation’s perspective is provided by the Osage Nation and the Eastern Band of Cherokee Indians. The South Carolina Institute of Archaeology and Anthropology; the University of Tennessee, Knoxville; the Illinois State Museum; and Indiana University share their viewpoints as institutions that house Indigenous Ancestral remains, cultural items, and archaeological collections and describe the initial impacts of the revised legislation on their programs. There are several key takeaways of its initial effects, including (1) an increased burden to Native Nations, given the substantial uptick in requests for consultation linked to new requirements for consent and the revised definitions of cultural items and research (although the end result of more consultations leading to repatriations is desired), (2) a disconnect between Native Nations and institutions regarding cultural item identification, (3) a strengthening of existing NAGPRA-related institutional policies and procedures, and (4) an emphasis on the importance of consultation between institutions and Native Nations to facilitate repatriation.